2019
DOI: 10.1016/j.cub.2019.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sperm Motility Mediates the Sex Ratio Drive Shaping Mouse Sex Chromosome Evolution

Abstract: SummaryThe mouse sex chromosomes exhibit an extraordinary level of copy number amplification of postmeiotically expressed genes [1, 2], driven by an “arms race” (genomic conflict) between the X and Y chromosomes over the control of offspring sex ratio. The sex-linked ampliconic transcriptional regulators Slx and Sly [3, 4, 5, 6, 7] have opposing effects on global transcription levels of the sex chromosomes in haploid spermatids via regulation of postmeiotic sex chromatin (PMSC) [8, 9, 10, 11] and opposing effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…These studies collectively show that mouse sex ratio is regulated by a competition between the ampliconic sex-linked transcriptional regulators Sycp3-like X-linked (Slx), Slx-like 1 (Slxl1), and Sycp3-like Y-linked (Sly) [12]. Loss or knockdown of Sly leads to up-regulation of X-linked genes and female-biased litters as a result of differential X/Y sperm motility [51], but the causal chain between Slx/Sly competition and sperm motility remains elusive. Could TLR7/8 be the missing link?…”
Section: Back To the Lab: What Can Mechanistic Studies Tell Us?mentioning
confidence: 93%
“…These studies collectively show that mouse sex ratio is regulated by a competition between the ampliconic sex-linked transcriptional regulators Sycp3-like X-linked (Slx), Slx-like 1 (Slxl1), and Sycp3-like Y-linked (Sly) [12]. Loss or knockdown of Sly leads to up-regulation of X-linked genes and female-biased litters as a result of differential X/Y sperm motility [51], but the causal chain between Slx/Sly competition and sperm motility remains elusive. Could TLR7/8 be the missing link?…”
Section: Back To the Lab: What Can Mechanistic Studies Tell Us?mentioning
confidence: 93%
“…This procedure allows producing over 90% of the male embryos following in vitro fertilization using ligand-selected highly motile spermatozoa. In another study using knockout (KO) mice model, Rathje et al (2019) reported that partial deletions of the Y chromosome (Yqdel) in males produce an equal number of X and Y spermatozoa. Although both sperm types are equally capable of fertilizing oocytes once at the site of fertilization, they exhibit a functional (motility and morphology) difference from each other that potentially skewed offspring sex ratio.…”
Section: Ratiomentioning
confidence: 99%
“…In a recent study, Umehara et al (2019) reported that ligand activation of TLR7/8 significantly decreased the motility of X spermatozoa (by altering ATP production) than that of Y. In addition, using the KO mice model, Rathje et al (2019) reported that Yqdel males (XYRIIIqdel) produced less motile Y spermatozoa compared to X.…”
Section: Motility and Swimming Patternmentioning
confidence: 99%
“…Although it is conceivable and intuitive that different phenotypes would have different chances of fertilizing ova, this connection is not always explicitly established. Empirical evidence for within-ejaculate competition with fitness consequences and thus evolutionary potential comes from some meiotic drivers [37,39,43]. Outside of these ( perhaps extreme) examples, indications that within-ejaculate competition has evolutionary potential comes from studies linking withinejaculate sperm selection to offspring fitness [44][45][46], though the underlying mechanisms remain somewhat elusive.…”
Section: Within-ejaculate Competition Driving Sperm Evolutionmentioning
confidence: 99%